Gold Salts Therapy in Respiratory Diseases - J. Benhamou, Ori-Michael; N. Oron, Maly; Waldman, Maor; Kalchiem-Dekel, Or (Current Respiratory Medicine Reviews, 2013)
Gold salts have been introduced as therapeutic agents in the late 19th century. The three gold salts approved for medical therapy auranofin, aurothiomalate, and aurothioglucose were shown to induce anti-inflammatory and immunosuppressive states via a myriad of mechanisms and used to be a mainstay of therapy for rheumatoid arthritis as well as other rheumatic and collagen vascular diseases before being supplanted by other less toxic agents. The research into the role of gold compounds in therapy of pulmonary disease have focused on asthma and demonstrated a significant anti-inflammatory effect as well as a mild steroid-sparing effect mainly in Japanese patients. These effects were offset by a wide array of adverse reactions, notably dermatological, hematological and renal effects. The main pulmonic adverse effect associated with gold therapy is interstitial pneumonitis which can present with an acute, subacute and chronic course. The role of gold salts in the therapeutic arsenal of COPD and interstitial lung diseases is less established. Recently published studies have investigated the role of aurothiomalate as an inhibitor of non-small cell lung cancer oncogene PKC iota.
Keywords: gold